Fasting vs. post-breakfast tabata exercise: implications for substrate metabolism and energy expenditure in young normal-weight women - Wang, Yongbo; Han, Yanbai; Cheng, Zhuoyue; Fan, Yaqing; Wang, Hongli (Frontiers in Physiology, 2026)
IntroductionWith the rising prevalence of obesity, time-efficient high-intensity exercises like Tabata training have gained significant attention for weight management. However, the effects of fasting versus post-breakfast states on substrate metabolism and energy expenditure during Tabata exercise remain unclear. This study aimed to investigate the metabolic responses to Tabata exercise under fasting and post-breakfast conditions in women, providing insight into how nutritional status acutely influences substrate utilization and energy expenditure.MethodsEighteen young normal-weight women (age 25.3 ± 3.1 years; BMI 20.9 ± 1.1 kg/m2)completed a randomized counterbalanced crossover trial, performing a 4-min Tabata workout under fasting (11–15 h overnight fast) and post-breakfast (90 min after a standardized meal) conditions. Gas exchange was continuously monitored to calculate fat oxidation, glucose oxidation, and energy expenditure.ResultsFat oxidation was significantly higher in the fasting condition at all analyzed time points, with the largest difference observed at 60 s (1.05 ± 0.18 vs. 0.61 ± 0.07 g/min, p < 0.001). In contrast, glucose oxidation was consistently higher in the post-breakfast condition, peaking at 150 s (3.65 ± 0.52 vs. 3.38 ± 0.46 g/min, p < 0.001). Total energy expenditure was also greater post-breakfast, reaching 10.18 ± 0.29 kcal/min at 120 s compared with 9.70 ± 0.39 kcal/min in the fasting condition (p < 0.001).ConclusionFasting and post-breakfast conditions elicit distinct acute metabolic responses during Tabata exercise in women. Fat oxidation was higher in the fasting state, while glucose oxidation and total energy expenditure were consistently higher in the post-breakfast state.